SARS-CoV-2 surveillance in decedents in a large, urban medical examiner’s office - Brouwer, Andrew F (Clin Infect Dis, 2020)
BACKGROUND: SARS-CoV-2 has become a global pandemic. Given the challenges in implementing widespread SARS-CoV-2 testing, there is increasing interest in alternative surveillance strategies. METHODS: We tested nasopharyngeal swabs from 1094 decedents in the Wayne County Medical Examiner’s office for SARS-CoV-2. All decedents were assessed by a COVID-19 checklist, and decedents flagged by the checklist (298) were preferentially tested. A random sample of decedents not flagged by the checklist were also tested (796). We statistically analyzed the characteristics of decedents (age, sex, race, and manner of death), differentiating between those flagged by the checklist and not and between those SARS-CoV-2 positive and not. RESULTS: A larger percentage of decedents overall were male (70% vs 48%) and Black (55% vs 36%) compared to the catchment population. Seven-day average percent positivity among flagged decedents closely matched the trajectory of percent positivity in the catchment population, particularly during the peak of the outbreak (March and April). After a lull in May to mid-June, new positive tests in late June coincided with increased case detection in the catchment. We found large racial disparities in test results: despite no statistical difference in the racial distribution between those flagged and not, SARS-CoV-2 positive decedents were substantially more likely to be Black (82% vs 51%). SARS-CoV-2 positive decedents were also more likely to be older and to have died of natural causes, including of COVID-19 disease. CONCLUSIONS: Disease surveillance through medical examiners and coroners could supplement other forms of surveillance and may serve as a possible early outbreak warning sign.